Regulatory role of T Helper 17 (TH17) cells in autoimmune diabetes - Norazmi, Mohd Nor (Pusat Pengajian Sains Perubatan, 2013)
Thl7 cells are thought to be involved in various autoimmune diseases such as multiple sclerosis, rheumatoid arthritis and experimental autoimmune encephalomyelitis. The role of Thl7 cells in the pathogenesis of autoimmune or type I diabetes (TID) was thus investigated using the non-obese diabetic (NOD) and the non-obese diabetic resistant (NOR) control mouse models. The expression of various cytokines in the Thl7 cells was assessed using flow cytometry following incubation with the peroxisome proliferator activated receptor gamma (PPARy) agonists, ciglitazone and 15-prostagalndin J2, and the PPARy antagonist, GW9662 to further delineate the influence of this immunoregulatory nuclear receptor on the Th 17 cell function. Basically, the constitutive level of the signature IL17A expression by Thl7 cells in NOD mice was more than that of NOR mice and that ciglitazone enhanced the expression of this cytokine in NOD mice whereas 15-PGJ2 and GW9662 had no effect. Interestingly, despite eliminating IFNy-expressing cells (Thl) at the start of culture, Th17 cells of NOD mice expressed high levels of this cytokine upon culture with ciglitazone suggesting that Thl7 may convert to Thl-like cells in TID in the presence of this PPARy agonist and may contribute to the pathogenesis of this autoimmune disease